Strongly unforgeable ID-based signatures without random oracles. (2nd July 2010) - Sato, Chifumi; Okamoto, Takeshi; Okamoto, Eiji
In this paper, we construct a strongly unforgeable ID-based signature scheme in the standard model (or without random oracles), with five signature parameters. The signature size of our scheme is smaller than that of other schemes based on varieties of the Diffie?Hellman (DH) problem or the discrete logarithm problem. The security of the scheme relies on the difficulty solving three problems related to the DH problem and a one-way isomorphism.